Deployment of internet of things-based cloudlet-cloud for surveillance operations - Edje E. Abel; Abd Latiff Muhammad Shafie; Weng Howe Chan (Institute of Advanced Engineering and Science, 2021)
This research proposes the design of internet of things (IoT) camera/toxic gas sensors for the surveillance of a nation’s borders. Also, a wearable radio frequency identification (RFID) tag with built-in body-temperature/heartbeat sensors, for monitoring the health status and locations of military personnel while on border patrol duty or in battlefield combats. Mobile micro-controllers are deployed to gather sensed data retrieved from the sensors/RFID tags and transmitted to a cloudlet situated at the command control center, located 200 meters away from the sensor devices. Consequently, sensed data are dispatch to the cloud data center when there is a need for offline data mining or analysis. The distinguishing feature of our proposed system from previous researches is that the health status and locations of troops (soldiers) are monitored while they are in border patrol duty or in battlefield combats. Also, the introduction of cloudlet services closer to the IoT sensor devices for collection of sensed data. This way, the sensed data or information gathered at the cloudlet will aid timely information retrieval that will speed up intelligence gathering for strategic military operations, especially in critical situations. This is an innovative attempt to apply IoT-enabled cloudlet-based cloud computing to support military operations.